2010
DOI: 10.1021/ef100505n
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Performance and Emission Characteristics of Biodiesel Fuel Containing Butanol under the Conditions of Diesel Engine Operation

Abstract: To expand the raw materials base for the production of biodiesel fuel, it is advantageous to make use of biobutanol (B) produced from renewable resources, which can be used in two ways as fuel for diesel engines: by direct inclusion into multicomponent fuel for diesel engines or by producing fatty acid butyl esters from rapeseed oil. Multicomponent fuels D70/B30, D70/B15/RME(RBE)15, and D50/B25/RME(RBE)25 meet the standards for fossil diesel fuel (D) and biodiesel fuel in terms of the main indicators of qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…In addition to alcohol-diesel blends, there were also attempts to use alcohol-biodiesel-diesel blends in diesel engine. Since the summary of alcohol-biodiesel [85,107,[120][121][122][123][124][125][126][127][128][129][130][131][132][133] and alcohol-biodiesel-diesel blends [84,89,95, has not been unraveled thus far, data pertaining to their engine characteristics has been outlined in Table 3.…”
Section: Blend Mode Operation Of Alcohol Based Fuelsmentioning
confidence: 99%
“…In addition to alcohol-diesel blends, there were also attempts to use alcohol-biodiesel-diesel blends in diesel engine. Since the summary of alcohol-biodiesel [85,107,[120][121][122][123][124][125][126][127][128][129][130][131][132][133] and alcohol-biodiesel-diesel blends [84,89,95, has not been unraveled thus far, data pertaining to their engine characteristics has been outlined in Table 3.…”
Section: Blend Mode Operation Of Alcohol Based Fuelsmentioning
confidence: 99%
“…The density of iso-butanol improves its energy density. Another important feature of iso-butanol is less sensitivity to water than ethanol, which tends to settle in layers when water is present (Lebedevas et al, 2010). The stoichiometric airfuel ratio of iso-butanol is lower than diesel, due to its oxygen content (Vertes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…AL15B5 and AL10B10 reduced the CO emission than AL20 about 19% and 26%, respectively because of more oxygen content. 35 Therefore, lower density and viscosity of the modied blends improved spray atomization and reduced fuel rich regions. On top of that higher oxygen content surely assisted complete oxidation of the fuels and reduced CO emission.…”
Section: Engine Emission Characteristicsmentioning
confidence: 99%
“…Altun et al 34 studied the effect of n-butanol on cottonseed biodiesel-diesel blend and reported that, emissions of NO x , HC and CO reduced in expense of higher BSFC. Lebedevas et al 35 investigated with butyl esters of rapeseed oil-diesel blend with the addition of 15-25% n-butanol and observed development on emission characteristics and overall efficiency. Mehta et al 36 added variable percentage of n-butanol with jatropha biodiesel-diesel blend and reported signicant drop in CO and NO emissions in expense of lower performance.…”
Section: Introductionmentioning
confidence: 99%